The Implementation of Internalizing Pancasila to Increase the Studentsâ Soft Skill Facing Global Chalenges At Elementary School - Supeni, Siti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this study is to modify the implementation of Pancasila (Civics)learning so that simply, children are trained to develop softskills that can then beused in their own lives through their activities as well as for others in facing globalchallenges in elementary schools (Sekolah Dasar). Through conductingResearchers build a complex and holistic picture, analyze the process, report adetailed view of the information, by conducting this research in a natural schoolenvironment.The research method through qualitative descriptive according to Creswell (2014),is the process of investigation and understanding based on different elementaryschool (SD) learning process in exploring the values of Pancasila. Data collectionat Sekolah Dasar in 3 provinces (West Java, Madura, and Bali), especially aboutinternalizing Pancasila in elementary school.The results of the research find the concept of the process in the form of descriptivein learning of Pancasila (Civics) modification, the implementation of the childrenare trained to develop soft skills which can then be used in their own life throughactivities done for themselves or for others in facing global challenges.Keywords: Softskill, Education, internalization, Pancasila